Likelihood ratios in psychological expert opinion, and their reception by professional judges. (October 2022) - Rassin, Eric; Arbiyah, Nurul; Boskovic, Irena; Otgaar, Henry; Merckelbach, Harald
In various countries, forensic scientists have begun to express their expert opinion in terms of the likelihood of observing the evidence under the primary and under an alternative hypothesis (i.e. the likelihood-ratio approach). This development is often confined to technical domains such as fingerprint analyses. In forensic psychological expertise, likelihood ratios are largely absent. In this contribution, we explain how forensic psychologists can employ likelihood ratios, and we describe two illustrating cases. We also present two studies in which we examined how (Dutch) professional judges appreciate psychological expertise framed in likelihood ratios. Findings suggest that judges ( N = 39) appreciate a fictitious expert witness report framed in likelihood-ratios similarly to an opinion framed one-dimensionally. Judges' ( N = 79) understanding of a psychological expert opinion framed in likelihood ratios was satisfactory as measured by self-report and an actual test We conclude that, as is custom in forensic technical domains, psychological expert opinion can be expressed in likelihoods. Two of the hypothesised flipsides, namely, lawyers' dislike of likelihoods, and their lack of proper understanding, may be surmountable.